DESIGN OF AUTOMATIC DIMMING LED CONTROL USING CURRENT CONTROLLED BUCK CONVERTER IN APPLICATION ON LTSHE SYSTEM IN ISOLATED AREAS - Yosia, Nuel
Holding the name as one of the largest archipelago countries in the world, Indonesia still faces one of the problems, namely electrification. In resolving this problem, the government has taken several steps. One such step is to provide Energy Efficient Solar Powered LED, which are supplied with renewable energy, in 3T areas that have not yet received electricity supply. LTSHE which is used today is still controlled manually by the lighting intensity. This research then aims to develop the existing LTSHE's system, and add automatic control using the Current Controlled Buck Converter.The control system under study will produce a constant output current and can be adjusted according to needs automatically. The simulation is done with Proteus software and is designed so that the output current can be changed by 7 steps of dimming (100%, 90%, 80%, 50%, 30%, 10%, and 50%) to adjust the power and intensity of the light produced according to the needs human. This LTSHE converter is also designed to be able to perform maneuver, which is setting the minimum intensity in conditions of overload interference or remove the load when the battery voltage touches the minimum value. From the simulation results, the converter circuit that was designed already meets the parameter specifications with a daily energy requirement of 99.36 Wh and with the expected specifications and parameters